Alternatif Strategi Pengembangan Agribisnis Tanaman Gambir Di Desa Toman Kecamatan Babat Toman Kabupaten Musi Banyuasin: Alternatif Strategi Pengembangan Agribisnis Tanaman Gambir - Ariyantini, Meri; Wildayana, Elisa; Antoni, Mirza; Adriani, Dessy (JURNAL AGRICA, 2025)
Gambier is the leading commodity of Musi Banyuasin Regency and the only regency in South Sumatra Province that actively cultivates and processes the gambier commodity. This study aimed to formulate alternative strategies for developing gambier agribusiness. This research was conducted in Toman Village, Babat Toman District, Musi Banyuasin Regency, South Sumatra Province. The research site was selected using a purposive sampling method. This study employed a survey approach involving eleven respondents, comprising experts, gambier farmers, and members of the general public in Toman Village. The data collected were analyzed qualitatively using a SWOT analysis framework. The results of the SWOT analysis indicate that the primary strategy for developing the gambier agribusiness falls within the first quadrant, representing the Strengths-Opportunities (SO) strategy. This strategy focuses on leveraging existing strengths to capitalize on and optimize available opportunities. The proposed actions include maximizing the application of cultivation technologies in gambier farming, expanding agro-industrial activities to enhance value-added processing, strengthening institutional support for gambier farmers, and promoting increased domestic consumption of gambier products. Through the implementation of this strategy, the main problem of gambier agribussiness in Toman Village, namely the low quality and limited inovation of gambier products, can be effectively addressed.